SISTEM MAINTENANCE TRANSFORMATOR 60 MVA PADA ELECTRIC ARC FURNACE (EAF) 7 SLAB STEEL PLANT 1 - Irwan anto Mina (President University, 2020)
Abstract.Preventive Maintenance is every activity undertaken to keep each component tool running in accordance with the expected conditions, through inspection, detection and prevention of total damage that is sudden (breakdown). Breakdown voltage or diode voltage drop is the minimum voltage value at the diode to be able to flow electric current. The research method used is qualitative research with a descriptive approach. In this study, the authors conducted data collection through: (1) direct observation (2) Retrieval of data using the Magger tool (3) literature study. The results of the study stated that in the examination and analysis of dissolved gas content (Dissolved gas analysis, DGA), to prevent the occurrence of: (partial) discharges, thermal failure (thermal faults), deterioration/deterioration of paper insulation/lamination. Insulation Resistance is a test to see the strength of insulation against physical and chemical damage. Damage that often occurs in the EAF 7 transformer is a breakdown voltage and an overheat transformer because the room temperature is not cold due to the transformer close to the cooking place or iron melting. Keywords. BDV, DGA, insulation resistance, maintenance, transformer